THE EFFECT OF GUAVA LEAF, PAPAYA LEAF, NONI LEAF, AND BETEL LEAF EXTRACTS ON ECTOPARASITES IN STRIPED SNAKEHEAD (Channa striata) - Muhammad Didi Syarif; Reffi Aryzegovina; Lisa Mayasari; Boni Ikhlas (Universitas Mataram, 2025)
The striped snakehead (Channa striata) is one of the most widely distributed freshwater fish species in Indonesia and has high economic value. One of the main problems in its aquaculture is ectoparasite infestation. Ectoparasites are parasites that attach to the external surfaces of fish and often cause significant losses. This study aimed to determine the effect of immersion in guava leaf, papaya leaf, noni leaf, and betel leaf extracts on reducing ectoparasite infestations in Channa striata. The experiment was conducted using a completely randomized design (CRD) with four treatments and three replications, namely guava leaf extract (P), papaya leaf extract (Q), noni leaf extract (R), and betel leaf extract (S). Fish were immersed for 20 days in extract solutions at a concentration of 1 g/L. Observations included survival rate, prevalence, and intensity levels. Ectoparasites were identified using the mucus scraping method and examined under a light microscope. Data were analyzed descriptively and tested using ANOVA. The results showed that the highest survival rate was recorded in the papaya leaf treatment (100%), while the lowest occurred in the guava and noni leaf treatments (86.6%). The only ectoparasite identified belonged to the genus Trichodina sp. The highest prevalence was found in the papaya leaf treatment (89%), whereas the lowest was in the betel leaf treatment (72%). Infection intensity ranged from 1.4 to 2 individuals per fish. Statistical analysis showed a significance value of 0.816 (>0.05), indicating that immersion with leaf extracts at this dosage did not significantly reduce the ectoparasite load in Channa striata.